Clariant unveils colour masterbatch range for water bottle caps…. Issue 2 (February 2018) - Unknown
Abstract : Clariant Masterbatches has launched a new line of colour masterbatches designed for use in the production of caps and closures for bottled water and other sensitive beverage applications. Available in a broad range of colours, Senseaction masterbatches are specially formulated, processed, tested and certified to be free from adverse flavour and odour tainting effects, the company reports.